Performance of Angora goats, mohair production, and farmer income in extensive livestock systems of north Patagonia, Argentina - Sacchero, Diego; Gonzalez, Ezequiel B.; Maurino, Julia; Lopez, Miriam; Cortes, Maria Victoria; Alvarez, Rocío; Bidinost, Franca (Frontiers in Animal Science, 2023)
Introduction In Argentina, mohair production is limited exclusively to the Patagonia region. This activity takes place under different biophysical conditions and with marked seasonality in the climatic conditions and productivity of natural grasslands. The present study aimed to analyze Angora goat performance, mohair production, and income in two contrasting environments of northern Patagonia. Methods Body weight (BW), body condition score (BCS), fleece weight (FW) and mohair samples were collected between the spring of 2019 and the autumn of 2022 on farms from the East and West regions. Fiber quality analyses included mean fiber diameter (MFD), percentage of medullated fibers (MED), and kemp fibers (KMP). Analysis of variance (ANOVA) was performed and the effects considered were region, shearing season (autumn and spring) and age. The income per shearing (IPS) was estimated based on the individual data and tender prices. Results In general, the BW of goats in the East was between 15% and 25% higher than that of the goats in the West (p < 0.01), whereas the FW difference between regions reached 25% to 32% in mature adult goats (p < 0.01). The autumn MFD was similar between regions (p >0.05) and higher than the spring MFD (p < 0.05). The KMP content in the West was two-fold higher (p <0.01) than that in the East (1.21%). Regarding the effect of the season, KMP and MED contents were higher in autumn than in spring (p <0.01). The IPS values were lower in spring. The highest IPS value was obtained at the age of two permanent incisors. Results showed that 70 of the 100 best-ranked goats by IPS were from the East. Discussion and conclusion This work offers new insights for understanding characteristics of mohair production in Argentine The results suggest that winter conditions in the West negatively impact the growth and mohair production during the spring shearing. In turn, a marked seasonality in climatic conditions and in the productivity of grasslands could explain the variability of the productive performance of goats between seasons. Efforts to improve mohair incomes should focus on producing heavier, less medullated fleeces rather than finer mohair.